Esophageal Foreign Bodies in Pediatric Patients: A Thirteen-Year Retrospective Study - Beata Rybojad; Grazyna Niedzielska; Artur Niedzielski; Ewa Rudnicka-Drozak; Pawel Rybojad (The Scientific World Journal)
We discuss clinical symptoms and radiological findings of variable esophageal foreign bodies as well as therapeutic procedures in Caucasian pediatric patients. A retrospective study of 192 cases of suspected esophageal foreign bodies between 1998 and 2010 was conducted. Data were statistically analyzed by chi-square test. A foreign body was removed from a digestive tract of 163 children aged 6 months to 15 years (mean age 4.9). Most objects were located within cricopharyngeal sphincter. Dysphagia occurred in 43%, followed by vomiting (29%) and drooling (28%). The most common objects were coins. Plain chest X-rays demonstrated aberrations in 132 cases, and in doubtful situations an esophagram test was ordered. In the group of thirty-seven patients whose radiograms were normal, esophagoscopy revealed fifteen more objects, which were eventually successfully removed. No major complications occurred. Esophagram should be a second X-ray examination if an object is not detected in plain chest X-ray. We recommend a rigid esophagoscopy under general anesthesia in doubtful cases as a safe treatment for pediatric patients.